Comparison Between Phenylephrine and Dopamine in Maintaining Cerebral Oxygen Saturation in Thoracic Surgery: A Randomized Controlled Trial. Issue 49 (December 2015) - Choi, Ji Won; JooAhn, Hyun; Yang, Mikyung; Kim, Jie Ae; Lee, Sangmin M.; Ahn, Jin Hee
Abstract : Abstract: Fluid is usually restricted during thoracic surgery, and vasoactive agents are often administered to maintain blood pressure. One-lung ventilation (OLV) decreases arterial oxygenation; thus oxygen delivery to the brain can be decreased. In this study, we compared phenylephrine and dopamine with respect to maintaining cerebral oxygenation during OLV in major thoracic surgery. Sixty-three patients undergoing lobectomies were randomly assigned to the dopamine (D) or phenylephrine (P) group. The patients' mean arterial pressure was maintained within 20% of baseline by a continuous infusion of dopamine or phenylephrine. Maintenance fluid was kept at 5 mL/kg/h. The depth of anesthesia was maintained with desflurane 1MAC and remifentanil infusion under bispectral index guidance. Regional cerebral oxygen saturation (rScO2 ) and hemodynamic variables were recorded using near-infrared spectroscopy and esophageal cardiac Doppler. The rScO2 was higher in the D group than the P group during OLV (OLV 60 min: 71 ± 6% vs 63 ± 12%; P  = 0.03). The number of patients whose rScO2 dropped more than 20% from baseline was 0 and 6 in the D and P groups, respectively ( P  = 0.02). The D group showed higher cardiac output, but lower mean arterial pressure than the P group (4.7 ± 1.0 vs 3.9 ± 1.2 L/min; 76.7 ± 8.1 vs 84.5 ± 7.5 mm Hg; P  = 0.02, P  = 0.02). Among the variables, age, hemoglobin concentration, and cardiac output were associated with rScO2 by correlation analysis. Dopamine was superior to phenylephrine in maintaining cerebral oxygenation during OLV in thoracic surgery.